2021
DOI: 10.3389/fphys.2021.713710
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Effects of Insulin on Human Urate Homeostasis

Abstract: Insulin and hyperinsulinemia reduce renal fractional excretion of urate (FeU) and play a key role in the genesis of hyperuricemia and gout, via uncharacterized mechanisms. To explore this association further we studied the effects of genetic variation in insulin-associated pathways on serum urate (SU) levels and the physiological effects of insulin on urate transporters. We found that urate-associated variants in the human insulin (INS), insulin receptor (INSR), and insulin receptor substrate-1 (IRS1) loci ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 74 publications
1
40
1
Order By: Relevance
“…In studies carried out on mice, insulin acts at the renal level favoring the expression of the uric acid reabsorption system and decreasing the expression of a major urate secretory transporter [ 77 ]. In humans, it was widely demonstrated that insulin values correlate with uric acid values and reduce urinary excretion of uric acid, although the mechanism underlying this phenomenon is not fully known [ 78 , 79 , 80 ]. The excessive concentration of uric acid in the cells causes an increase in the activity of xanthine oxidase and causes damage to the mitochondria with a consequent increase in the production of reactive oxygen species [ 81 ].…”
Section: Biomarkers Predictive Of Metabolic Syndrome and Cardiovascul...mentioning
confidence: 99%
“…In studies carried out on mice, insulin acts at the renal level favoring the expression of the uric acid reabsorption system and decreasing the expression of a major urate secretory transporter [ 77 ]. In humans, it was widely demonstrated that insulin values correlate with uric acid values and reduce urinary excretion of uric acid, although the mechanism underlying this phenomenon is not fully known [ 78 , 79 , 80 ]. The excessive concentration of uric acid in the cells causes an increase in the activity of xanthine oxidase and causes damage to the mitochondria with a consequent increase in the production of reactive oxygen species [ 81 ].…”
Section: Biomarkers Predictive Of Metabolic Syndrome and Cardiovascul...mentioning
confidence: 99%
“…2 ) [ 54 ]. Insulin can selectively activate its UA transport function [ 55 ]. Bahn et al [ 54 ] found that the expression of SLC22A13 in chickens was gender dependent, and the female was higher than the male.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SLC2A9 SNPs may have a protective effect on gout, but its severe hypouricemia and its complications may endanger the lives of patients. Non-additive genetic interaction between SLC2A9 and insulin related genes also affects SUA [ 55 ]. Moreover, this effect is most obvious in women, which is consistent with the greater effect of SLC2A9 on UA in women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations